Chemical proteomic profiling reveals protein interactors of the alarmones diadenosine triphosphate and tetraphosphate - Lena Krüger (Nature Portfolio, 2021)
Diadenosine polyphosphates (ApAs) are involved in cellular stress signaling but only a few molecular targets have been characterized so far. Here, the authors develop Ap n A-based photoaffinity-labeling probes and use them to identify Ap3A and Ap4A binding proteins in human cell lysates.